Exploring the benefits of collaborative prewriting in a Thai EFL context. (November 2019) - McDonough, Kim; De Vleeschauwer, Jindarat; Crawford, William J.
Although second language (L2) collaborative writing research has demonstrated that texts composed collaboratively are more accurate than individually-written texts, few studies have explored whether collaborative prewriting yields similar benefits. This study investigated whether collaborative prewriting, i.e. interacting with peers during the prewriting phase followed by individual writing, led to higher accuracy, complexity, or analytic ratings than individual prewriting. It also explored the relationship between these text features and student talk during collaborative prewriting. English L2 university students in Thailand ( n = 57) were randomly assigned to write a problem and solution paragraph with either collaborative or individual prewriting. Their texts were analysed in terms of accuracy (errors/word) and complexity (coordination and subordination), and were rated using analytic rubrics (content, organization, language). Transcripts of the collaborative prewriting discussions were analysed in terms of the topic of student talk (content, organization, language, task management, off-task talk). The results showed that the collaborative prewriting texts were more accurate and received higher ratings than the individual prewriting texts. Furthermore, there was a significant correlation between prewriting time and accuracy. Implications for the use of collaborative prewriting tasks in settings for English as a foreign language (EFL) are discussed.